Prophylaxe in der Hämophilie-BTherapie - Siegmund, B.; Richter, H.; Pollmann, H. (Hämostaseologie, 2010)
Based on the documentation from patients with severe haemophilia B (FIX : C <1%) in home treatment the positive effect of continuous prophylaxis compared to on demand treatment was investigated over one year in a retrospective study from a single treatment centre (Centre for Haemostaseology Muenster).The advantage of the reduction in the number of bleeding episodes by 90% was opposed by a threefold higher consumption of FIX concentrates and a fourfold higher exposure of the patients to intravenous injections.
Keywords: Haemophilia B; treatment on demand; continuous therapy; prophylaxis; factor IX